The Man Who Filmed Nessie: Tim Dinsdale and the Enigma of Loch Ness by Angus Dinsdale - Bauer, Henry (Journal of Scientific Exploration, 2014)
The strongest evidence that Loch Ness Monsters are real animals is the film taken in 1960 by Tim Dinsdale. It remains unique and remains the evidence that debunkers have most determinedly attempted to undermine. In trying to assess the merits of the film and of the criticisms, one wants to see the film itself and to learn about the circumstances of the filming and the trustworthiness of the photographer. This book by Dinsdale’s youngest child is illuminating about the circumstances and the photographer, and the book’s website (http://www.themanwhofilmednessie.com/) presents the film in informatively annotated fashion. The book includes more than 30 pages of color photos showing people and historical events associated with the search for Nessie.